Effect of Firm Size, Profitability and Capital Intensity on Effective Tax Rate (ETR): Pengaruh Ukuran Perusahaan, Profitabilitas dan Intensitas Modal Terhadap Effective Tax Rate (ETR) - Aulia, Nur Afni; Ernandi, Herman (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to determine the size of the company, profitability and capital intensity affect the effective tax rate on Manufacturing Companies listed on the Indonesia Stock Exchange. The period used in this study is 3 (three) years, starting from 2017 to 2019. This study uses a form of quantitative research method. The sampling technique in this study used a purposive sampling method which resulted in 23 manufacturing companies according to existing criteria with a three-year observation period, so that the total sample was 69 companies. The data analysis technique used is multiple linear regression. In addition, there are also descriptive statistical tests and classical assumption tests. In this study, the hypothesis was tested using the t test (partial) and the coefficient of determination (R Square). The statistical program in this study uses SPSS version 18.0. The results obtained based on multiple linear regression analysis indicate that the variables of firm size, profitability and capital intensity affect the effective tax rate. Simultaneously, the variables of firm size, profitability and capital intensity have been shown to have an effect on effective tax rates.